The Resurgence of Introgression Breeding, as Exemplified in Wheat Improvement - Hao, Ming; Zhang, Lianquan; Ning, Shunzong; Huang, Lin; Yuan, Zhongwei; Wu, Bihua; Yan, Zehong; Dai, Shoufen; Jiang, Bo; Zheng, Youliang; Liu, Dengcai (Frontiers in Plant Science, 2020)
Breeding progress in most crops has relied heavily on the exploitation of variation within the species’ primary gene pool, a process which is destined to fail once the supply of novel variants has been exhausted. Accessing a crop’s secondary gene pool, as represented by its wild relatives, has the potential to greatly expand the supply of usable genetic variation. The crop in which this approach has been most strongly championed is bread wheat (Triticum aestivum), a species which is particularly tolerant of the introduction of chromosomal segments of exotic origin thanks to the genetic buffering afforded by its polyploid status. While the process of introgression can be in itself cumbersome, a larger problem is that linkage drag and/or imperfect complementation frequently impose a yield and/or quality penalty, which explains the reluctance of breeders to introduce such materials into their breeding populations. Thanks to the development of novel strategies to induce introgression and of genomic tools to facilitate the selection of desirable genotypes, introgression breeding is returning as a mainstream activity, at least in wheat. Accessing variation present in progenitor species has even been able to drive genetic advance in grain yield. The current resurgence of interest in introgression breeding can be expected to result in an increased deployment of exotic genes in commercial wheat cultivars.